2018
DOI: 10.21091/mppa.2018.3028
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Profile and Performance Demands of Elite Hip-Hop Dancers: Breaking and New Style

Abstract: New style is more comparable to other theatrical dance genres, with a lower relative mean VO2 demand, whilst break dance is shorter in duration, allowing a higher cardiorespiratory demand and generating significant levels of blood lactate. This difference is also reflected in the dancers' cardiorespiratory profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 20 publications
2
41
2
2
Order By: Relevance
“…Through a cross-sectional design the current study has provided the first physiological data on musical theatre performers. The cardiorespiratory profiles of musical theatre performers indicated aerobic fitness levels higher than that previous reported for other dance theatre genres [4,5,7,26,27] and similar to hip hop dancers [15] . The anaerobic threshold (AT) for MT dancers was similar to that reported for classical ballet principal and artist dancers [27].…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Through a cross-sectional design the current study has provided the first physiological data on musical theatre performers. The cardiorespiratory profiles of musical theatre performers indicated aerobic fitness levels higher than that previous reported for other dance theatre genres [4,5,7,26,27] and similar to hip hop dancers [15] . The anaerobic threshold (AT) for MT dancers was similar to that reported for classical ballet principal and artist dancers [27].…”
Section: Discussioncontrasting
confidence: 57%
“…Cardiorespiratory data (oxygen consumption and heart rate) on dance performance indicated that dancers are exercising close to their maximal cardiorespiratory capacities with a greater stress on the lactate system compared to class and rehearsal [3,7,12,15]. Time motion analysis indicates that this is due to differences in the work to rest ratio; performance was generally characterised as having fewer and/or shorter rest periods accompanied by higher work intensities [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though there has been a start in investigating Breaking from a physiological 16,17 , psychological 18,19 and biomechanical 7,20 perspective, injury epidemiological data are still sparse 15 . The aim of this study was to collect self-report breaking-specific injury data using a 12-month recall methodology that also includes information on participants', lifestyles and training experiences.…”
mentioning
confidence: 99%